Pharmacologic Management of Perioperative Pulmonary Hypertension - Cheng, Julie W. (2014)
Perioperative pulmonary hypertension can originate from an established disease or acutely develop within the surgical setting. Patients with increased pulmonary vascular resistance are consequently at greater risk for complications. In spite of the various specific therapies available, the ideal therapeutic approach in this patient population is not currently clear. This article describes the basic principles of perioperative pulmonary hypertension and reviews the different classes of agents used to promote pulmonary vasodilation in the surgical setting.